The Constructing of Teaching Package Using Moral Tales to Develop Reading for Main Ideas for Prathomsuksa 3 Students at Municipality School 1 (Wat Phrom Wihan), Mae Sai District, Chiang Rai Province - เทพโพธา, ชยาทิพย์; จันทร์เรือง, ยุพิน; เท็งตระกูล, อัญชลี (Ganesha Journal, 2019)
The objectives of this study were: 1) to construct and examine the efficiency of reading for main idea instructional package using 8-Morality Tale for Prathomsuksa 3 students based on 80/80 efficiency criteria; 2) to compare the student’s learning achievement on reading for main idea before and after implementation of the constructed instructional package; and 3) to assess the students’ satisfaction towards the constructed instructional package. The sample group, selected by simple random sampling, was 33 Prathomsuksa 3/3 students from Municipality School 1 (Watphromvihan), Mae Sai District, under Chiang Rai Primary Educational Service Area Office 3 in their semester 2/2018. The research instruments were: 1) 8 sets of instructional package on reading for main idea skills, 2) achievement test, 3) learning management plan, and 4) satisfaction evaluation form. The statistics for data analysis were mean, percentage, standard deviation, and t-test. The results were: 1) The constructed instructional package on reading for main idea for Prathomsuksa 3 students of Municipality School 1 (Watphromvihan) showed the efficiency at 86.95/80.00 which were higher than that of the 80/80 standard. 2) The students’ learning achievement indicated that the posttest scores was higher than those of the pretest as the pretest were 15.03 (37.58%) but the posttest were 36.82 (92.05%) that revealed the progress score at 21.79 (54.47%). 3) The students’ satisfaction towards the constructed instructional package on reading for main idea of Prathomsuksa 3/3 at Municipality School 1 (Watphromvihan), in overall, was at the high level ( = 4.94, S.D. = 0.20) which agreed with the hypothesis.